Analysis of the Algerian severe weather event in November 2001 and its impact on ozone and nitrogen dioxide distributions - Thomas, Werner; Baier, Frank; Erbertseder, Thilo; Kästner, Martina (2003)
An analysis of the severe weather event in November 2001 over the western Mediterranean is presented focusing on satellite-based trace gas measurements from the Global Ozone Monitoring Experiment (GOME) on board the European Remote Sensing Satellite (ERS-2). This study is supplemented by a synoptic analysis and simulations of the three-dimensional stratospheric chemical transport model ROSE. Arctic air masses moved rapidly from Scandinavia to the Iberian peninsula and were mixed with subtropical air over the still warm Mediterranean Sea. This caused severe thunderstorms and extreme rainfall along the coasts of Morocco and Algeria and later on the Balearic Islands. Associated with the meridional transport an intrusion of stratospheric air below 3 km above sea level was observed. The maximum potential vorticity (PV) derived from UK Meteorological Office analysis data was about 9.3 potential vorticity units (pvu) at 330 K at the equatorward position of 35°N. These very high values went along with remarkably enhanced total ozone levels obtained from GOME backscatter measurements of collocated GOME/ERS-2 overpasses. Further investigation of GOME data showed unusually high levels of nitrogen dioxide (NO2) above the western Mediterranean. We present a new method to derive the tropospheric content of nitrogen dioxide (NO2) from a combination of satellite measurements and results of a chemical transport model. We show that about two-third of the total atmospheric content of nitrogen dioxide in the observed plume is found in the troposphere, due to lightning activity, advection and vertical transport in the thunderstorms from the planetary boundary layer (PBL) to atmospheric levels above clouds.